Ocular Dominance Plasticity of Areas 17 and 21a in the Cat - Wang, Jian; Ni, Zheyi; Jin, Anqi; Yu, Tiandong; Yu, Hongbo (Frontiers in Neuroscience, 2019)
The visual system is organized in a parallel and hierarchical architecture. However, the plasticity in hierarchical neural networks is controversial across different response features and at different levels. In this study, we recorded areas 17 and 21a, earlier and intermediate stages of the visual cortex in the cat, respectively, by single-unit recording and intrinsic-signal optical imaging. We found that ocular dominance (OD) plasticity evoked by monocular deprivation (MD) was stronger in area 21a than in area 17 in the critical period, and this plasticity became weaker but still persisted in area 21a while it disappeared in area 17 beyond the critical period. These results suggest a diversified functional plasticity along the visual information processing pathways in a hierarchy neural network.